Research of the Residual Stress Generation and Influence Factor of Grinding Tooth Surface of Spiral Bevel Gear - Zhou Jing; Ming Xingzu (Jixie chuandong)
The residual stress of spiral bevel gear on the tooth surface is produce by the comprehensive effect of various factors of grinding conditions.The mathematical model of the grinding basic parameters of the effects on grinding residual stress,grinding heat and grinding force.Based on the finite element 3D model of single tooth,the finite element simulation and analysis of residual stress of spiral bevel gear grinding,and the test shows this method is feasible.The results show the residual stress present in the spiral bevel gear tooth surface,while the residual tensile stress in the tooth,the grinding residual stress is connected with grinding depth,wheel speed,extended speed and grinding fluid.The reducing of grinding residual stress can effectively prevent grinding cracks.